Discourse on the Multicultural Policy in Sweden in Light of the Charlie Hebdo Terrorist Attack - Kobierecka, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
Multicultural policy has recently been undergoing a marked crisis and is subject to wide criticism. In the light of recent terrorist attacks it is often highlighted that the reason for such situations might be too much openness towards foreigners. Most European countries are changing their immigration and integration policies limiting their social security and restricting the possibilities of an influx of immigrants. Sweden, which is perceived as one of the most open and tolerant states in Europe also faces new challenges concerning the future of its multicultural policy. The crisis in tolerance towards foreigners is quite visible and it is obvious that the social moods in this state are evolving. Therefore, the aim of the article is to analyze changes in the attitude towards Swedish immigration and its integration policy in the light of the attack on the Charlie Hebdo weekly offices.